Pengaruh Kualitas Kehidupan Kerja Karyawan, Pelatihan dan Kepemimpinan terhadap Kinerja Karyawan Fox Hotel Pekanbaru - Rahayu Setianingsih; Ayu Safitri; Alum Kusumah; M. Alhudhori (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study was to determine the effect of the quality of employee work life, training and leadership on employee performance at Fox Hotel Pekanbaru. This research was conducted at Fox Hotel Pekanbaru with a research sample of 76 employees of Fox Hotel Pekanbaru. The sampling technique used was saturated sampling in which the entire population in this study was used as the research sample. The results of this study indicate that: 1). The quality of employee's work life has a significant effect on employee performance; 2). Training has a significant effect on employee performance; 3). Leadership has a significant effect on employee performance; 4). The quality of employee work life, training and leadership simultaneously affect employee performance.